'Falling off the radar' of public health: The case of uninsured Chinese patients in Vienna, Austria. Issue 9 (September 2019) - Seidler, Yuki; Novak-Zezula, Sonja; Trummer, Ursula
Highlights: We present health data of uninsured Chinese migrants in Austria as first-of-its-kind evidence. Uninsured Chinese migrants in Austria seek health care from service providers outside the public health system. Comorbidities were high (75%). The most frequently diagnosed single disease was type II diabetics for both sexes (18%). NGOs play an important role in providing continuous care for this group and in collecting relevant data. A trusting relationship between science and practice are essential for evidence-based public health policy making. Abstract: In public health policy debates, the 2015–2016 refugee crisis made visible that even in European welfare states with (close to) universal health coverage there are specific vulnerable groups with highly limited access to health care. Among them is a population of so-called 'undocumented' or 'irregular' migrants who have no regular status of residence and falls off the radar of publicly funded health care services and thus from the public health surveillance systems. The aim of our study is to provide the first-of-its-kind evidence on the characteristics, health problems and health care needs of one such vulnerable group in Austria – Chinese migrants residing in Vienna without a regular status. Medical records of 74 uninsured assumingly undocumented Chinese patients were analysed. The data was provided by a Non-governmental organisation (NGO) which delivers primary care to uninsured people in Vienna. The most frequently diagnosed health problems clustered around cardiovascular and metabolic-related diseases (hypertension and diabetics) and there was a high burden of multiple chorionic non-communicable diseases. Further efforts and resources are needed for collecting more data in a systematic way. A trusting relationship between science and practice and a cooperative relationship between and among the government agencies and NGOs are essential for evidence-based public health policy making.